2012
DOI: 10.1021/bc3001276
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chitosan Oligosaccharide-Modified Gold Nanorods for in Vivo Targeted Delivery and Noninvasive Imaging by NIR Irradiation

Abstract: In the present study, we demonstrate the synthesis and applications of multifunctional gold nanorod-based probes for specific targeting and noninvasive imaging based on localized heating generated by gold nanorods after NIR irradiation. The structural design of the probe consists of MUA (11-mercaptoundecanoic acid)-capped gold nanorods covalently linked with low-molecular-weight chitosan oligosaccharide (M(w) ~5000) via carbodiimide (EDC) coupling agent. This surface modification is performed for complete repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…The anti-EGFR-AuNRs were observed at depths up to 100 μm in the tumors. Selective targeting and accumulation of chitosan oligosaccharide-modified AuNRs were also observed in vitro via TPL imaging studies in human oral adenosquamous carcinoma cell line (CAL 27) 11, consistent with in vivo targeting studies performed via NIR laser irradiation in CAL 27 xenograft tumors (Figure 3A).…”
Section: Aunrs As Imaging Agentssupporting
confidence: 80%
“…The anti-EGFR-AuNRs were observed at depths up to 100 μm in the tumors. Selective targeting and accumulation of chitosan oligosaccharide-modified AuNRs were also observed in vitro via TPL imaging studies in human oral adenosquamous carcinoma cell line (CAL 27) 11, consistent with in vivo targeting studies performed via NIR laser irradiation in CAL 27 xenograft tumors (Figure 3A).…”
Section: Aunrs As Imaging Agentssupporting
confidence: 80%
“…Photothermal imaging of CAL 27 xenografted tumors displayed significant temperature increments (~up to 71 °C) specifically at the tumor microenvironment after NIR irradiation, which is well suited for PTT. Modified nanoparticles also did not display any associated toxic effect in vivo [64]. Cheng et al reported a study of ultrasmall (10 nm) dendrimer-stabilized gold nanorods (DSAuNRs) for photothermal destruction of cancer cells.…”
Section: Imaging and Photo-thermal Therapy Using Gold Nanoparticlesmentioning
confidence: 99%
“…Both Au and Ag NPs with various shapes can serve as the LSPR core for the core-shell structure. However, only Au NR will be considered as an example in the present paper owing to its tunable absorption peak, which can be moved into the NIR region by increasing the corresponding aspect ratio [33]. Moreover, the Au NR is surrounded by the gain medium that overlaps spatially with the hot-spot of the local plasmonic field and whose gain spectrum overlaps spectrally with the resonant absorption.…”
Section: Simulations and Discussionmentioning
confidence: 99%